Experimental investigations into the influence of biofilms and environmental factors on short‐term microtopographic fluctuations of supratidal sandstone. Issue 7 (14th February 2019) - Yuan, Runjie; Kennedy, David M.; Stephenson, Wayne J.; Gómez‐Pujol, Lluís
Abstract: In this study laboratory experiments were used to explore the role of biofilms, formed by lithobiontic microorganism communities, in causing hourly surface changes of supratidal sandstone and the potential linkage to long‐term rock decay. To isolate the influence of individual environmental factors (temperature and humidity) on rock surface changes (expansion and contraction), a colonized (biofilm‐covered) and a non‐colonized sandstone block (biofilm‐free) underwent the same univariate microclimatic simulations closely controlled by an environmental chamber. Simulations were run under three different light conditions, with a natural light lamp on, on and off at 20‐min intervals and off, to investigate the impact of light on rock surface dynamics. Measured with a traversing micro‐erosion meter (TMEM), two‐hourly microtopographic fluctuations of these two sandstone blocks were compared in the same environment. Induced by microclimatic variations, surface movements of significantly higher magnitude (12–120% under varying tempeature and 121–154% under varying humidity) and different change patterns were observed on the colonized block, indicating the primary role of biofilm in driving microtopographic fluctuations of supratidal sandstone. However, thermally driven changes of similar magnitude and pattern were observed on both surfaces, suggesting other mechanisms also operating on the non‐colonized rock surface in this process. Due to the sensitivity of biofilm microorganism communities to light, the magnitude and pattern of surface changes was impacted by light condition. Because biofilms increased the magnitude and number of cycles of expansion and contraction of the experimental rock surface, we propose that lithobiontic biofilms facilitate the detachment of grains and granular disintegration on the rock surface, consequently contributing to rock decay and accelerating the rate of breakdown of supratidal rock. This short‐term episode therefore needs to be superimposed on longer term studies to fully understand the role of biofilms in rock surface change. © 2019 John Wiley & Sons, Ltd. Abstract : The microtopography of two sandstone blocks with and without colonization of biofilms were measured with a traversing micro‐erosoin meter (TMEM) under different simulated environmental conditions. Two‐hourly microtopographic fluctuations of supratidal sandstone were mainly induced by the colonized biofilms and influenced by environmental factors. By increasing the magnitude and number of cycles of expansion and contraction, lithobiontic biofilms were proposed to play an erosive role in rock decay at hourly scale.